Barney The Good Egg
The Good Egg: When the kids find a mysterious, colorful egg in the park, Barney takes them on a trip to Kenyato find out what kind of animal could have laid the egg. While in Kenya, they meet Ayira whp introduces them to many people, cultures and animals of Kenya！A Bird of a Different Feather: Barney takes the kids to Hawaii on a quest for a bird of paradise.While there, they meet some friends, learn new Hawaiian words, make a Hawaiian lei and dance a hula! Eventually, Barney and his friends find a bird of paradise, but it's not quite what they were expecting!